2010
DOI: 10.2527/jas.2009-2246
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ruminal protein degradability and frequency of supplementation on nitrogen retention, apparent digestibility, and nutrient flux across visceral tissues in lambs fed low-quality forage1

Abstract: Two experiments were conducted to determine the effect of ruminal protein degradability and supplementation frequency on intake, apparent digestibility, N retention, and nutrient flux across visceral tissues of lambs fed a low-quality forage diet. In both experiments, wethers were fed a basal diet of mature crested wheatgrass hay (4.2% CP) for ad libitum consumption plus 1 of 4 supplements: 1) a high RDP supplement provided daily (RDP-D), 2) the high RDP supplement provided on alternate days (RDP-A), 3) a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 32 publications
1
5
0
1
Order By: Relevance
“…Those authors observed that even on the days the animals did not receive supplementation, NH 3 levels were above the 8.0 and 10.0 mg/dL of rumen fluid suggested by Detmann et al (2014) and Leng (1990) as optimal values for appropriate fermentation in tropical conditions. A lower frequency of supplementation increases the endogenous synthesis of urea to be recycled and return to the rumen environment to be used by the microorganisms, particularly on days without supplementation (ATKINSON et al, 2010). A lack of effects of lower supplementation frequency has been observed on the body retention of nitrogen compounds (MORAES et al, 2010;RUFINO, 2015), which can also explain the maintenance of the animal performance in relation to the cattle supplemented daily, as found in the current experiment.…”
Section: Resultssupporting
confidence: 52%
“…Those authors observed that even on the days the animals did not receive supplementation, NH 3 levels were above the 8.0 and 10.0 mg/dL of rumen fluid suggested by Detmann et al (2014) and Leng (1990) as optimal values for appropriate fermentation in tropical conditions. A lower frequency of supplementation increases the endogenous synthesis of urea to be recycled and return to the rumen environment to be used by the microorganisms, particularly on days without supplementation (ATKINSON et al, 2010). A lack of effects of lower supplementation frequency has been observed on the body retention of nitrogen compounds (MORAES et al, 2010;RUFINO, 2015), which can also explain the maintenance of the animal performance in relation to the cattle supplemented daily, as found in the current experiment.…”
Section: Resultssupporting
confidence: 52%
“…Segundo esses autores, embora aumentos na digestibilidade total do nitrogênio contribuam para aumentar o nitrogênio retido, a maior parte desta resposta decorre da redução na excreção de NUR. Desta forma, a menor frequência de suplementação aumenta a síntese endógena de ureia para ser reciclada e retornar ao ambiente ruminal para ser usada pelos microrganismos, particularmente em dias sem suplementação (Atkinson et al, 2010). Assim, com base nesta afirmativa, se maior quantidade de NS for desviada para essa função produtiva, a excreção de NUR é diminuída.…”
Section: Resultsunclassified
“…According to literature, SBM is higher in rumen degradable crude protein (74.9%, Cozzi et al, 1995) than MLM (48.6%, Makkar and Becker, 1996). Atkinson et al (2010) evaluated the effect of ruminal protein degradability and supplementation frequency on intake, apparent digestibility, N retention, and nutrient flux across visceral tissues of lambs fed a low-quality forage diet. They concluded that the release of ammonia N by the portal-drained viscera (PDV) was reduced in alternate-day-supplemented lambs compared with lambs receiving rumen degradable protein daily.…”
Section: Discussionmentioning
confidence: 99%